STRUGGLE IN JUN’ICHI WATANABE’S NOVEL BEYOND THE BLOSSOMING FIELDS - Sri Wirda; Purwarno Purwarno (JOURNAL OF LANGUAGE, 2019)
This research is about the struggle of the first character named Ogino Ginko in reaching her dream to be a female doctor and help other women who have the same illness as she suffers in a novel, Beyond the Blossoming Fields, written by Watanabe Jun`ichi, published in 1970. This research is conducted by descriptive qualitative method, and one of the significant theories used in this research is proposed by Centeno (2014: 136) who claims that struggles are exactly what we need in our life. It means struggle is something crucial in our life. The finding of this research shows that the protagonist is successful in her struggle to be a doctor. She becomes the first female doctor in Japan, and after she opens a clinic, there are so many woman patients coming to her clinic, and most of them are contracted with the illness as she suffers. She also becomes the inspiration for other women in Japan to become woman doctors.